Interface dominated deformation transition from inhomogeneous to apparent homogeneous mode in amorphous/amorphous nanolaminates. (10th February 2022) - Chen, Z.Q.; Li, M.C.; Cao, J.S.; Li, F.C.; Guo, S.W.; Sun, B.A.; Ke, H.B.; Wang, W.H.
Highlights: A length-scale-dependent mechanical properties were observed in the A/ANLs. The hardness of A/ANLs was closely related with their deformation mode. The deformation mode of A/ANLs was determined by the interface. Abstract: The amorphous/amorphous nanolaminates (A/ANLs) have aroused great attentions owing to their tunable structure and enhanced mechanical properties. However, the plastic deformation mechanism of A/ANLs have yet been clarified. Here, we systematically examined the mechanical properties and deformation behavior of series of NiNb/ZrCuNiAl A/ANLs via nanoindentaion test. It was found that both the amount and morphology of amorphous/amorphous interface (A/AIs) played crucial roles in the plastic deformation of A/ANLs. Less and straighter A/AIs facilitated multiple shear banding deformation, of which the hardness increased with decreasing layer thickness, as the A/AIs hindered the propagation of shear bands (SBs). Whilst, more and wavier A/AIs promoted homogeneous deformation, of which the hardness stayed at a much lower value and was relatively irrelevant with the layer thickness, for the promoted activation of shear transformation zones by A/AIs. Our results provide guidance for modifying the mechanical properties of amorphous alloys with interface engineering design. Graphical abstract: Image, graphical abstract